Social Inequality in Access to Education in Remote Areas: A Case Study of Talaud Islands Regency, North Sulawesi - Bimo Arianto; Syamsir Galib (Generasi Sains Indonesia, 2024)
This paper looks at social inequality in education provision in Talaud Islands Regency, North Sulawesi in terms of educational inequality between cities and rural settlements. Through the use of a qualitative case study method, the study identifies some of the factors which act as a barrier to access such as a small number of secondary schools, poor teacher qualification, absence of education infrastructure and poverty as well as the absence of educational provision and great levels of drop outs. Information was collected by conducting interviews with stakeholders working locally on schooling but also by direct visitations of school premises. The results indicate a serious problem of the equal educational provision, and the rural students have more difficulties in proceeding with learning as a result of geographical isolation and economic background. The article highlights the importance of specific policy decisions that may help upgrade infrastructure, train the staff, and provide financial assistance to remote inhabitants. Suggestions have been made such as investing in schools infrastructure, providing a reward to those teachers who can work in rural areas, and economic obstacles to a student continuing his/her education.